Takbir ZawÄid dalam Salat Id Prespektif K.H. Lanre Said al-Bugisi - Syandri, Syandri; Saifullah bin Anshor; Patahuddin, Askar; Miranto, Agus (NUKHBATUL 'ULUM: Jurnal Bidang Kajian Islam, 2020)
This research aimed to identify zawÄid takbir in id prayer according to K.H Lanre Said al-Bugisi perspective. This research was a qualitative descriptive study using the library research method with juridical-normative and philosophical approaches. The results of this study indicate that in determining shari law, K.H. Lanre Said used several approaches and methods. The method of iá¹£tishÄbul hÄl, muqaranÄt al-maáº“Ähib, tarjih, and the principle of "al-khurÅ«ju minal khilÄf. Based on this method K.H. Lanre Said al-Bugisi rejects the existence of zawÄid takbir (additional takbir) in the id prayers arguing that all narrations describing zawÄid takbir are of a weak degree. Therefore, the takbir for the id prayer must be returned to its original form, which is one takbir, just as the Friday prayer is only one takbir. In addition, K.H. Lanre Said al-Bugisi built his opinion using the method of al-aqly (reason) in which he argued that zawÄid takbir was not needed because it would be one of the causes for the loss of solemnity in prayer. This research has a positive implication which is to reveal the shari law-setting method according to K.H. Lanre Said al-Bugisi and his arguments against the existence of zawÄid takbir in id prayers.